Towards Inclusive Entrepreneurship: Addressing Constraining and Contributing Factors for Women Entrepreneurs in South Africa - Patrick Ebong Ebewo; Cecile Schultz; Mphoreng Magdeline Mmako (Administrative Sciences)
Women entrepreneurs are increasingly recognised as pivotal contributors to economic growth, poverty alleviation, and employment generation, particularly in developing economies like South Africa. This study explores the contributing and constraining factors that shape the future of women’s entrepreneurship in South Africa through the lens of Institutional Theory. Using a qualitative methodology, in-depth interviews were conducted with nine (9) women entrepreneurs affiliated with a Centre for Entrepreneurship Development. The findings highlight key enabling factors, such as mentorship, education, supportive policies, collaboration, and government intervention programmes, which equip women entrepreneurs with the skills, networks, and resources needed to thrive. However, significant barriers persist, including financial exclusion, societal norms, ineffective policies, and psychological constraints such as low entrepreneurial self-efficacy. The study concludes that aligning institutional support across the regulatory, normative, and cultural-cognitive dimensions is essential for fostering an inclusive entrepreneurial ecosystem. Recommendations include simplifying access to funding, expanding mentorship opportunities, and addressing systemic cultural and policy barriers to create a more equitable and supportive environment for women entrepreneurs.